COPPER SULPHATE INDUCED NEURONAL HISTOLOGICAL CHANGES IN THE FRESHWATER SNAIL BELLAMYA BENGALENSIS (L) - N. A. KAMBLE,; S. R. LONDHE, (The Bioscan, 2011)
Present study was carried to investigate the nuropathological effect of induced copper sulphate in cerebral ganglion of the freshwater snail Bellamya bengalensis. Histopathological and ultrastructural changes found hypertrophy, hypotrophy, shrinkage in the neuronal cells with include degeneration in neurons leading to changes in axonal processes. Ganglionic histopathology were compared and discussed with normal neuronal cells of snail Bellayma bengalensis.